PEMANFAATAN MEDIA SOSIAL UNTUK MENINGKATKAN PENDAPATAN USAHA RUMAHAN LAUNDRY IBU RUMAH TANGGA DI KECAMATAN SEKIP JAYA PALEMBANG - Ery Hartati; Usnia Wati Keristin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The purpose of this activity is to provide partners with understanding, provisioning, and training in the aspects of production, marketing and business promotion, capital, and bookkeeping, so that their businesses can develop and provide better income. The target to be achieved is to address issues such as: low production capacity, quality and product durability.  So that the objectives, targets, and outcomes in this program can be realized properly, the implementation mechanism consists of 4 stages, namely preparation and planning (socialization and programming), implementation, evaluation and monitoring, and reflection. All stages are carried out by participatory methods through observation, interview, FGD, and joint decision making techniques. Through these methods the services offered by Bandung Home Laundry services become more varied and innovative, thus attracting consumers. The results of a series of 4 stages are increasing the value of assets and income of Housewife Laundry Business, increasing the quantity and quality of Housewife Laundry services being marketed, increasing marketing of quality service products.